2014
DOI: 10.4172/2327-5073.1000173
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Class I Integrons and Antimicrobial Resistance among Clinical Staphylococci Isolates from a Turkish Hospital

Abstract: Purpose: Methicillin-resistant staphylococci (MRS) are increasingly significant in the hospital setting due to multidrug resistance. Integrons are genetic elements that can play a role in the dissemination of antimicrobial resistance. While their role is well established in gram-negative bacteria, less is known about the presence of integrons in gram-positive bacteria. Our aim was to investigate the presence of class 1 integrons in clinical MRS isolates. Methods:One hundred clinical MRS isolates were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
7
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
7
7
3
Order By: Relevance
“…Xu et al (6)in China, reported class 1 integron in 53% of the S. aureus isolates. In contrast to our results, Guney et al (35) from Turkey revealed that none of the isolates harbored class 1 integron. The high prevalence of class 1 integron in our study strongly supports suggestions that class 1 integron may serve as reservoirs of antimicrobial resistance in MRSA strains.…”
Section: Discussioncontrasting
confidence: 99%
“…Xu et al (6)in China, reported class 1 integron in 53% of the S. aureus isolates. In contrast to our results, Guney et al (35) from Turkey revealed that none of the isolates harbored class 1 integron. The high prevalence of class 1 integron in our study strongly supports suggestions that class 1 integron may serve as reservoirs of antimicrobial resistance in MRSA strains.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the literature, MRSA strains are resistant not only to beta-lactams but also to macrolides, lincosides, and aminoglycosides (6,8,18). In the present study, the majority of the MRSA isolates were resistant to ampicillin (100%), ciprofloxacin (94.5%), gentamicin (98.2%), erythromycin (90.9%), tetracyclin (87.3%), and clindamycin (98.2%), which is in line with the findings reported in Iran (8), Croatia (17), and Turkey (19). The rate of resistance to tested antibiotics, with the exception of amikacin among MRSA isolates, was higher than those among MSSA isolates, which is in accordance with the findings reported by Yu et al (20).…”
Section: Discussionsupporting
confidence: 91%
“…In this survey, the presence of class 1 and 2 integrons was confirmed in 45 (56.3%) and 15 (18.7%) isolates, respectively. These findings are consistent with previous studies in which the rate of detection of integron class 1 was more than integron class 2 (6,28,29). In the study of Xu et al in China, out of 30 S. auerus isolated from environment and surgical patients, 16 (53%) clinical and environmental isolates were positive for the class 1 integrase gene (6).…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted by Guney et al that investigated the presence of class 1 integron in MRSA isolated from a 1150-bed training and research hospital located at Black Sea region in Turkey, one hundred clinical MRSA isolates were investigated. The result revealed that none of the isolates harbored class 1 integron (29). The high prevalence of class 1 integron in our survey strongly demonstrated that class 1 integron might serve as a reservoir for antimicrobial resistance in Iranian S. aureus strains.…”
Section: Discussionmentioning
confidence: 58%